2020
DOI: 10.1021/acs.energyfuels.0c01222
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous Displacement at Solvent–Immobile Hydrocarbon Interfaces

Abstract: Concerns over the environmental impacts of thermal production methods for bitumen and heavy oil have led to the exploration of alternative technologies including solvent-assisted production methods. While solvent-assisted production methods have been studied extensively, the apparent diffusion coefficients of the penetrating solvent 1–2 orders of magnitude greater than those predicted for Fickian diffusion applicable to liquid mixtures are required to match production histories. “Surface renewal” and “sloughin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…However, the excellent aqueous solubility would prevent the mass transfer of chemical reagents into the oil phase to make effective collisions with the organometallic compounds in the oil bulk, making it an interface reaction. Also, the liquid–liquid interface properties, such as apparent diffusion coefficients, solvent penetration, and phase separation rate, have great impacts on reactions. Therefore, there is an irreconcilable contradiction between hydrophilicity and lipophilicity of chemical reagents during chemical demetallization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the excellent aqueous solubility would prevent the mass transfer of chemical reagents into the oil phase to make effective collisions with the organometallic compounds in the oil bulk, making it an interface reaction. Also, the liquid–liquid interface properties, such as apparent diffusion coefficients, solvent penetration, and phase separation rate, have great impacts on reactions. Therefore, there is an irreconcilable contradiction between hydrophilicity and lipophilicity of chemical reagents during chemical demetallization.…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not explain why the increased solvent fraction in the diluted oil would not lead to a higher velocity and, consequently, higher dispersion. Recently, Wang et al 38 demonstrated that mass transfer rates in a drainage process can be enhanced significantly in gravity unstable configurations, which lead to convection, surface renewal, and cyclic sloughing. Hence, both convection and gravity instability can contribute to enhanced mass transfer and more rapid bitumen recovery.…”
Section: Introductionmentioning
confidence: 99%